2014
DOI: 10.1128/jvi.02877-13
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Peptidyl-Prolyl cis / trans Isomerase Pin1 Regulates Reactivation of Kaposi's Sarcoma-Associated Herpesvirus from Latency

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) causes Kaposi's sarcoma and primary effusion lymphoma. KSHV-infected cells are predominantly latent, with a subset undergoing lytic reactivation. Rta is the essential lytic switch protein that reactivates virus by forming transactivation-competent complexes with the Notch effector protein RBP-Jk and promoter DNA. Strikingly, Rta homolog analysis reveals that prolines constitute 17% of conserved residues. Rta is also highly phosphorylated in vivo. We previously dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 70 publications
(109 reference statements)
0
32
0
Order By: Relevance
“…To assess the effect of IFI16 KD on TPA-mediated KSHV lytic reactivation, BCBL-1 cells were transduced with a lentivirus containing ShIFI16 or a control lentivirus. Forty-eight hours later, cells were induced with TPA (20 ng/ml), and total RNA was isolated after 0, 3,6,9,12,24,36,48,72, and 96 h, as indicated (Fig. 3A).…”
Section: Ifi16 Knockdown In Pel Cells Results In Global Increasesmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effect of IFI16 KD on TPA-mediated KSHV lytic reactivation, BCBL-1 cells were transduced with a lentivirus containing ShIFI16 or a control lentivirus. Forty-eight hours later, cells were induced with TPA (20 ng/ml), and total RNA was isolated after 0, 3,6,9,12,24,36,48,72, and 96 h, as indicated (Fig. 3A).…”
Section: Ifi16 Knockdown In Pel Cells Results In Global Increasesmentioning
confidence: 99%
“…The control of the latent and lytic phases of herpesviruses is a complex interplay and orchestration between viral and host factors. Host factors such as STAT3 (21), KAP1/TRIM28 (22), retinoblastoma (Rb) (23), and the cellular peptidyl-prolyl cis/trans isomerase Pin1 (24) were recently found to play very important roles in this latent-tolytic life cycle switch of herpesviruses.…”
mentioning
confidence: 99%
“…In silico alignment analysis of the transcription activation factor (TAF) 50 superfamily revealed that Rta homologs share a consensus of 134 amino acids (residues conserved between KSHV Rta and at least one additional member). Proline consists of 38 of these amino acids, accounting for 16.7% of all of Rta’s conserved residues ( Figure 4 ) [ 40 , 166 ]. The high degree of conservation supported their putative functional significance.…”
Section: Function Regulation and Dysregulation Of Pin1 Isomerase mentioning
confidence: 99%
“…In our report, we demonstrated an interaction between cellular isomerase Pin1 and KSHV lytic switch Rta. We showed that Pin1 is expressed and active in infected PEL cells after lytic cycle induction, and that Pin1 directly interacts with Rta in vitro and in infected cells, most likely at one of Rta’s putative conserved Pin1-recognition (pS/T-P) motifs [ 166 ]. Pin1 did not, however, interact with the essential Rta cofactor and Notch effector RBP-Jk by GST pulldown assay [ 166 ].…”
Section: Function Regulation and Dysregulation Of Pin1 Isomerase mentioning
confidence: 99%
“…The reasons for this fascinating conduct are unknown but likely involve viral chromatin compaction, epigenetic modifications [15,16,19] and interactions with host factors [33][34][35][36][37] . Consistent with our results, previous studies have vividly demonstrated that only a limited number of herpesviral genomes give rise to progeny virus in studies using a Brainbow cassette to trace the lineage of incoming viral herpesviral genomes during de novo lytic infections [38,39] .…”
Section: Research Highlightmentioning
confidence: 99%